Optical transmission body and illumination device

The optical transmission with a fluorine resin-based clad material and high-index core material addresses durability issues by ensuring strong adhesion, maintaining light emission and reducing loss, even under stress.

JP2025014956APending Publication Date: 2025-01-30KURABE IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023117953
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Conventional optical transmissions face issues with durability due to peeling of the clad material from the core material under external forces or thermal history, affecting light emission characteristics.

Method used

An optical transmission with a tube-like structure comprising a clad material made of fluorine resin containing an adhesive functional group, such as ethylene-tetrafluoroethylene copolymer with a carboxylate anhydride residue, and a core material with a higher refractive index, ensuring strong adhesion and durability.

Benefits of technology

The solution prevents peeling of the clad and core materials, maintaining light emission characteristics and reducing optical transmission loss, even under external forces or thermal stress, with improved flexibility and brightness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014956000001_ABST
    Figure 2025014956000001_ABST
Patent Text Reader

Abstract

To provide an optical transmission body which is excellent in durability, and an illumination device using the same.SOLUTION: An optical transmission body is composed of a tube-like clad material, and a core material which is stored in the clad material and has a higher reflective index than that of the clad material, wherein the clad material is composed of a fluororesin containing an adhesive functional group. In the optical transmission body, the fluororesin to which the adhesive functional group is introduced is an ethylene-tetrafluoroethylene copolymer containing a carboxylic acid anhydride residue. In the optical transmission body, a melting point of the clad material is 190°C to 240°C. In the optical transmission body, fine particles are dispersed in the clad material. An illumination device is composed of a light source, and the optical transmission body.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical transmission element suitable for lighting applications and an illumination device using the same, and relates to an optical transmission element having excellent durability. [Background technology]

[0002] Conventionally, various optical transmitters have been proposed that are made of a core material and a clad material and emit light incident on at least one end in the length direction from the circumferential direction (side surface). Related techniques include, for example, Patent Documents 1 to 5 and Patent Documents 6 and 7. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 3974112: Kurabe [Patent Document 2] JP2004-333539A: Kurabe [Patent Document 3] Patent No. 4194099: Kurabe [Patent Document 4] Patent No. 4928760: Kurabe [Patent Document 5] Patent No. 6376948: Kurabe [Patent Document 6] JP 2006-317844 A: 3M [Patent Document 7] Patent No. 5341391: 3M DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] The optical transmission bodies described in the above Patent Documents 1 to 5 have already been put into practical use by the applicants and have been evaluated to a certain extent by the market. However, in recent years, there has been a further demand from the market for improved durability in various situations. In particular, the fluororesin used as the cladding material in conventional optical transmission bodies has a property of being difficult to bond with other materials, so that when excessive external force is applied to the optical transmission body or when the optical transmission body is subjected to repeated heat history, the cladding material and the core material may peel off. When the cladding material and the core material peel off, the light emission characteristics at that portion change, and the core material may protrude from the cladding material at the end, changing the connection state between the light source and the optical transmission body.

[0005] The present invention has been made to solve the problems of the prior art, and an object of the present invention is to provide an optical transmission body having excellent durability and an illumination device using the same. [Means for solving the problem]

[0006] In order to achieve the above-mentioned object, the optical transmission element according to the present invention is an optical transmission element comprising a tubular clad material and a core material housed in the clad material and having a higher refractive index than the clad material, characterized in that the clad material is made of a fluororesin containing an adhesive functional group. It is also considered that the fluororesin into which the adhesive functional group has been introduced is an ethylene-tetrafluoroethylene copolymer containing a carboxylic anhydride residue. The melting point of the cladding material may be in the range of 190°C to 240°C. It is also possible that fine particles are dispersed in the clad material. Moreover, a lighting device according to the present invention comprises a light source and the above-mentioned light transmitting body. Effect of the Invention

[0007] According to the present invention, the clad material and the core material are well bonded, so that the clad material and the core material do not peel off even when an external force is applied to the optical transmission body or when the optical transmission body is subjected to repeated thermal history, resulting in excellent durability. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a partially cutaway side view showing the optical transmission element according to the present embodiment. [Diagram 2] 11 is a graph showing the results of measuring luminance in the length direction in this embodiment and the comparative example. [Diagram 3] 1 is a table showing the results of measuring chromaticity in the length direction in this embodiment and the comparative example. [Figure 4] 1 is a table showing bending reaction force measurement results in the present embodiment and the comparative example. [Diagram 5] FIG. 2 is a diagram showing the results of measurement by infrared spectroscopy in this embodiment.

[0009] In particular, the optical transmission body in the present invention is preferably composed of a clad material and a core material contained in the clad material and having a higher refractive index than the clad material. With such an optical transmission body, total reflection of light is likely to occur at the interface between the clad material and the core material, and the brightness can be made sufficient even at a position considerably distant from the light source. In addition, if the core material is amorphous, the transparency can be further improved, so that the optical transmission loss can be reduced. In addition, it is also possible to form a light-transmitting resin coating on the outer periphery of the clad material.

[0010] The constituent material of the clad material is not particularly limited and may be any material that is flexible and easy to mold, such as plastics and elastomers. For example, polyethylene, polyamide, polyvinyl chloride, silicone resin, natural rubber, polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkoxyethylene (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene copolymer, Examples of the fluorine-based polymer include vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene propylene rubber, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene-perfluoromethyl vinyl ether copolymer, polyperfluorobutenyl vinyl ether, TFE-perfluorodimethyl dioxolane copolymer, fluorinated alkyl methacrylate copolymer, and fluorine-based thermoplastic elastomer. These may be used alone or in a blend of two or more.

[0011] Among the materials constituting the clad material described above, for example, fluororesins such as vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer (THV), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene-perfluoromethylvinyl ether copolymer, ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer are preferred because of their excellent transparency and mechanical properties. Also, fluororesins containing adhesive functional groups are preferred. The adhesive functional group is a group having reactivity and polarity, and examples thereof include a carboxyl group, a carboxylic anhydride residue (a residue formed by dehydration condensation of a carboxyl group), an epoxy group, a hydroxyl group, an isocyanate group, an ester group, an amide group, an aldehyde group, an amino group, an alkoxysilyl group, a hydroxysilyl group, a cyano group, a sulfonic acid group, and an ether group. The adhesive functional group may be included as an end group, may be grafted, may be included as a part of the structure of a side chain, or may be included as a part of a block unit of a block copolymer. By including an adhesive functional group, it is possible to adhere well to the core material or the light-transmitting resin coating, so that even when the optical transmission body is bent with a small bending radius, when the optical transmission body is repeatedly bent, when an external force such as pressure is applied, or when a repeated heat history is applied, the cladding material and the core material, or the light-transmitting resin coating and the cladding material are not peeled off, and the durability is excellent. Among these, those containing a carboxylic anhydride residue are particularly preferable because they have particularly improved adhesion. The melting point of the clad material is preferably 190° C. to 240° C. If it is 240° C. or lower, molding is easy because high temperatures are not required during extrusion molding compared to general fluororesins such as PTFE and FEP, while if it is 190° C. or higher, defects such as deformation when the product is used at high temperatures can be prevented.More specific examples include "Fluon (registered trademark) LM-ETFE AH series (manufactured by AGC Corporation)", "Fluon (registered trademark) LM-ETFE LH-8000 (manufactured by AGC Corporation)", and "Neoflon (registered trademark) EFEP RP series (manufactured by Daikin Industries, Ltd.)".

[0012] As the constituent material of the core material, for example, those used as light-transmitting materials can be selected, such as transparent grades of acrylic resins, methacrylic resins, polyurethane resins, polyester resins, silicone resins, polystyrene resins, vinyl chloride resins, cycloolefin resins, polypropylene resins, acrylonitrile-butadiene-styrene resins, polycarbonate resins, etc. Among these materials, from the viewpoints of flexibility and aging characteristics under high temperature and high humidity, it is preferable to use a polymer polyol and a polymer of a hydroxyl group-reactive polyfunctional compound as one of the constituent components.

[0013] Examples of polymer polyols include polyoxyalkylene polyols such as polyoxypropylene polyols, polyethylene glycols, and polytetramethylene ether glycols, modified polyoxyalkylene polyols such as urethane-modified polyether polyols and silicone-modified polyether polyols, polyether ester copolymer polyols, polycarbonate polyols, and copolymers or mixtures thereof. Among these, polyoxypropylene polyols are preferred because they exhibit excellent ejection characteristics even under high temperature and high humidity conditions and in hot water.

[0014] Examples of the hydroxyl group-reactive polyfunctional compound include compounds having an N-carbonyl lactam group, halides, compounds having an isocyanate group, and compounds having a functional group derived from an isocyanate group. Examples of compounds having an isocyanate group include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates. Examples of compounds having a functional group derived from an isocyanate group include blocked isocyanates obtained by blocking isocyanates with lactams or other known methods, and compounds having isocyanurates obtained by polymerizing isocyanate groups with known methods. These compounds can be used alone or in a blend of two or more. Among these compounds, compounds having an isocyanate group or compounds having a functional group derived from an isocyanate group are preferred because they exhibit excellent side emission characteristics under high temperature and high humidity conditions and even in hot water. Among compounds having an isocyanate group, alicyclic polyisocyanates are more preferred. Among the compounds having a functional group derived from an isocyanate group, those having an isocyanurate bond are more preferred.

[0015] A light-transmitting resin coating may be formed on the outer periphery of the clad material. For example, a flexible methacrylic resin is preferably used as a constituent material of the light-transmitting resin coating. The flexible methacrylic resin is basically a copolymer of methyl methacrylate and an alkyl (meth)acrylate ester such as methyl acrylate, ethyl acrylate, butyl acrylate, propyl acrylate, hexyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, phenyl acrylate, or benzyl acrylate. For example, methacrylic acid esters other than methyl methacrylate, such as ethyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate; vinyl acetate; aromatic vinyl monomers, such as styrene, p-methylstyrene, o-methylstyrene, m-methylstyrene, α-methylstyrene, and vinylnaphthalene; nitriles, such as acrylonitrile and methacrylonitrile; α,β-unsaturated carboxylic acids, such as acrylic acid, methacrylic acid, and crotonic acid; maleimide compounds, such as N-ethylmaleimide, N-cyclohexylmaleimide, No-chlorophenylmaleimide, and N-tert-butylmaleimide; and vinyl cyanide compounds, such as acrylonitrile and methacrylonitrile, may be appropriately polymerized with the flexible methacrylic resin. The flexible methacrylic resin may also contain a polyolefin resin. Examples of polyolefin resins include ethylene-based polymers such as high-density polyethylene, low-density polyethylene, ethylene-1-octene copolymer, ethylene-acrylic acid copolymer, ethylene-zinc acrylate copolymer, ethylene-acrylic acid ester copolymer, ethylene-methacrylic acid ester copolymer, ethylene-vinyl acetate copolymer, and hydrolyzates of ethylene-vinyl acetate copolymer; propylene-based polymers such as polypropylene, ethylene-propylene copolymer, and propylene-1-butene copolymer; conjugated diene polymers such as butadiene polymer and isoprene polymer; and hydrogenated conjugated diene polymers such as hydrogenated butadiene polymer and hydrogenated isoprene polymer. In addition, other polymers and additives may be contained as necessary.Examples of additives that can be contained include mineral oil softeners such as paraffinic oil and naphthenic oil for improving fluidity during molding; inorganic fillers such as calcium carbonate, talc, titanium oxide, silica, clay, barium sulfate, and magnesium carbonate for improving or increasing heat resistance and weather resistance; inorganic or organic fibers such as glass fiber and carbon fiber for reinforcement; heat stabilizers; antioxidants; light stabilizers; adhesives; tackifiers; plasticizers; antistatic agents; and foaming agents. The amount of these additives may be appropriately set according to the required characteristics. In addition, it is also possible to blend various dyes, pigments, or fluorescent agents within a range that provides a sufficient amount of emitted light to set the luminous color of the light transmitting body to a specific color. It is preferable to add the above additives in such an amount that the light transmittance in the visible light region at a thickness of 0.25 mm of the flexible methacrylic resin is 80% or more. This makes it possible to suppress the scattering and absorption of light inside the light-transmitting resin coating, thereby reducing transmission loss, and also makes it possible to emit light of the color intended in the design with vivid colors when colored light is emitted from a light source of a specific color. The light transmittance in the visible light region is measured in accordance with JIS-K7105 (1981). Of course, in addition to flexible methacrylic resin, the above-mentioned polymer materials can be used as long as they are transparent.

[0016] The cross-sectional shape of the light-transmitting resin coating may be not only circular but also irregular, and a shape that allows easy and reliable fixing when arranged on a flat surface is preferably selected as the irregular shape. For example, a shape that increases the contact area between the mounted portion and the light transmitting body, a shape that allows the light transmitting body to be hooked and fixed to the mounted portion, etc., are conceivable, and specifically, various shapes such as a triangle, a rectangle, a pentagon, a hexagon, a semicircle, a shape that combines a circle and a rectangle, etc. are conceivable. In addition, when a light-transmitting resin coating is not formed, it is also conceivable to form the cladding material into various shapes such as those described above.

[0017] By dispersing fine particles in any or all of the core material, clad material, and light-transmitting resin coating, a light scattering function can be imparted, and a side emission type light transmission body that emits incident light from the circumferential direction (side surface) can be obtained. In particular, dispersing fine particles in the clad material is preferable from the viewpoint of uniformity of light emission. In addition, the clad material may be colored due to adhesive functional groups contained in the clad material. In such a case, the coloring is less noticeable when the fine particles are scattered in the clad material than when the fine particles are dispersed in the core material. In order to color the clad material due to adhesive functional groups, it is possible to add various dyes, pigments, fluorescent agents, etc. to any or all of the core material, clad material, and light-transmitting resin coating. For example, when the clad material is colored yellow, it is possible to add a known so-called bluing agent.

[0018] Examples of microparticle materials include inorganic materials such as glass microparticles such as quartz glass and multi-component glass, metal oxide particles such as aluminum oxide, titanium oxide, magnesium oxide, and zinc oxide, sulfate particles such as barium sulfate, and carbonate particles such as calcium carbonate. Next, examples of organic materials include polymethyl methacrylate (PMMA) particles, polystyrene particles, polycarbonate particles, and the like, as well as particles of fluoropolymers such as polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkoxyethylene (PFA), polychlorotrifluoroethylene (PCTFE), tetrafluoroethylene-ethylene copolymer (ETFE), polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene propylene rubber, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer (THV), polyperfluorobutenyl vinyl ether, TFE-perfluorodimethyldioxolane copolymer, fluorinated alkyl methacrylate copolymer, and fluorine-based thermoplastic elastomer. These may be appropriately selected in consideration of the constituent material of the core material used, the non-fluidizing treatment conditions, the length of the light transmission body, the amount of light emitted from the side, the conditions of use, or the true specific gravity, shape, particle size, concentration, refractive index, etc. of the fine particles. In particular, zinc oxide in the form of a hexagonal plate is preferable as the fine particles. Ordinary zinc oxide fine particles are irregular and amorphous because they are manufactured through a pulverization process and a baking process. Here, the crystal structure of zinc oxide is a hexagonal wurtzite type crystal structure in which a hexagonal close-packed lattice of zinc is superimposed on a hexagonal close-packed lattice of oxygen atoms that are moved vertically from the hexagonal close-packed lattice by 3 / 8. Therefore, when ultrafine particles of zinc oxide are aged in an aqueous zinc salt solution, the crystals grow into a specific hexagonal plate shape. By dispersing zinc oxide in such a shape, light absorption is unlikely to occur on the surface of the fine particles, and the luminance is unlikely to decrease even when the distance from the light source is far away, and uniform light emission can be obtained from any position.

[0019] The particle size of the fine particles is preferably an average particle size within the range of wavelengths from visible light to near infrared light. The wavelengths from visible light to near infrared light in the present invention refer to those in the range of 360 to 2500 nm (see JIS-K0210 (2007) and JIS-Z8120 (2001)). In particular, the average particle size is preferably within the range of wavelengths of visible light. The wavelengths of visible light in the present invention refer to those in the range of 360 to 830 nm (see JIS-Z8120 (2001)). When the particle size of the fine particles is equal to or larger than the wavelength of visible light, the scattering of light is in the Mie scattering region. The intensity of Mie scattering is maximum when the particle size and the wavelength are almost equal, so the closer the average particle size of the fine particles is to the wavelength of visible light, the higher the luminance is, and this is preferable. In addition, in Mie scattering, as the particle size increases, the directivity toward the incident direction of light becomes stronger, and light is not scattered much to the side or rear. Therefore, by keeping the average particle size of the particles within the wavelength of near infrared rays, particularly by not exceeding the range of the wavelength of visible light, the light is sufficiently scattered to the sides and rear, and uniform light emission can be obtained from any angle. In addition, if the average particle size of the particles is less than the wavelength of visible light, the effect of Rayleigh scattering appears, and the light emission appears bluish, which is not preferable. In addition, if the particle size becomes too small, there is a problem that it is difficult to disperse uniformly. The average particle size can be measured by measuring the unidirectional diameter of a sufficient number of particles (for example, 250 or more) in an image enlarged by an electron microscope, etc., and calculating the average value of the cumulative distribution. In particular, the hexagonal plate-shaped zinc oxide particles obtained by the above-mentioned crystal growth can be obtained with a uniform particle size, so that such an actual particle size measurement can obtain a sufficiently accurate value.

[0020] In addition, in the portion of the optical transmission body where the fine particles are dispersed, the fine particles are preferably dispersed at a ratio of 0.10 to 0.20 vol%. If the ratio is less than 0.10 vol%, the light scattering is insufficient, and the overall brightness tends to decrease. If the ratio exceeds 0.20 vol%, the light scattering is increased near the light source, and sufficient brightness may not be obtained at a position away from the light source.

[0021] The optical transmission element according to the present invention may not have the above-mentioned fine particles dispersed therein. In that case, the light is not emitted from the side surface of the optical transmission element, but from the end surface of the optical transmission element.

[0022] Any or all of the core material, clad material, and light-transmitting resin coating may contain a weather-resistant additive. Specific embodiments include adding a weather-resistant additive to the core material, adding a weather-resistant additive to the clad material, applying a weather-resistant additive to the inner surface of the clad material, applying a weather-resistant additive to the outer surface of the clad material, and adding a weather-resistant additive to the light-transmitting resin coating. Examples of weather-resistant additives include ultraviolet absorbers, light stabilizers, antioxidants, and heat stabilizers, which may be used in combination. More specific examples include salicylic acid derivatives, benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, hindered amine-based light stabilizers, semicarbazone-based light stabilizers, phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants.

[0023] The optical transmission body of the present invention is manufactured by using the above-mentioned constituent materials, for example, by the method shown below. First, the material constituting the above-mentioned clad material is molded into a long, tubular shape by a known method such as extrusion molding. When fine particles are dispersed in the clad material, it is possible to knead the material constituting the clad material with the fine particles and then extrusion molding. With this clad material wound around a bobbin or the like, at least a polymer polyol and a hydroxyl group-reactive polyfunctional compound in a fluid state are filled inside the clad material. Here, "at least" means that the polymer polyol and the hydroxyl group-reactive polyfunctional compound are sufficient as constituent components, and it is naturally assumed that the material contains a third component. It is also possible to mix and fill fine particles at this time. Furthermore, the polymer polyol and the hydroxyl group-reactive polyfunctional compound are reacted, for example, by heating, and subjected to a non-fluidizing treatment. According to the above method, the core material is not altered by exposure to heat when extrusion coating the light-transmitting resin, and the characteristics are not deteriorated when the core material is made into an optical transmission body, which is preferable. Here, it is also possible to increase the viscosity of the mixture of the polymer polyol and the hydroxyl group-reactive polyfunctional compound (including fine particles in some cases) in a fluid state by subjecting them to a pretreatment such as heating before filling the inside of the cladding material. This can shorten the time for the non-fluidization treatment, and when making a side emission type optical transmission body, it is possible to make the dispersion state of the fine particles more uniform.

[0024] The method of filling the mixture of the polymer polyol in a fluid state, the hydroxyl group-reactive multifunctional compound, and the fine particles inside the clad material can be, for example, a method using a vacuum pump or a tube pump, or a method of filling under pressure. Another method is, for example, a method of filling the mixture of the polymer polyol in a fluid state and the hydroxyl group-reactive multifunctional compound (including fine particles in some cases) at the same time when forming the clad material into a tube shape by extrusion molding. By doing this, it is possible to continuously manufacture a long optical transmission body.

[0025] Depending on the type of material used, the core material may be formed simply by extrusion molding of the core material. In this case, various methods can be used, such as a method in which the core material is extruded, and then the cladding material and the light-transmitting resin coating are extruded around the core material in sequence, or a method in which the core material, the cladding material, and the light-transmitting resin coating are extruded simultaneously in any combination.

[0026] In forming the light-transmitting resin coating, for example, a light-transmitting resin may be extruded and coated on the outer periphery of a clad material molded into a tube shape using an extrusion die designed to have a desired cross-sectional shape, and then a polymer polyol in a fluid state and a hydroxyl group-reactive multifunctional compound, etc. may be filled and non-fluidized. Alternatively, a polymer polyol in a fluid state and a hydroxyl group-reactive multifunctional compound, etc. may be filled in the clad material first, non-fluidized, and then the light-transmitting resin coating may be formed by extrusion coating. However, when forming the light-transmitting resin coating later, care must be taken to prevent the core material from being altered by the heat of extrusion coating. When forming the light-transmitting resin coating later, even if the core material has a tendency to bend during the non-fluidization treatment, it can be straightened.

[0027] As a method for forming the light-transmitting resin coating, in addition to the method of forming it on the outer periphery of the clad material by extrusion coating, there is also a method of covering the outer periphery of the clad material with a light-transmitting resin coating previously formed into a tube shape, etc. In this case, however, it is necessary to firmly adhere the clad material and the light-transmitting resin coating to prevent any peeling.

[0028] In the present invention, it is also conceivable to provide a lighting device by disposing a light source at at least one end of the optical transmission body. As the light source, a conventional light-emitting element, for example, an LED (light-emitting diode) or an LD (laser diode), can be used. The light emission color and the number of light sources to be installed are not particularly limited. For example, by appropriately selecting an LED having a light emission color of red, blue, green, yellow, orange, white, etc., or by combining a plurality of LEDs, it is possible to obtain various colors and increase the amount of light.

[0029] When a side-emitting optical transmitter that emits incident light from the circumferential direction (side) is used as the optical transmitter, it is also possible to arrange the light source not only at one end of the optical transmitter but at both ends. In this way, it is possible to obtain light emission with a higher luminance, and by using light sources with different luminous colors at each end, it is possible to emit light with a gradually changing color along the length of the lighting device, enabling a variety of decorative expressions. EXAMPLES

[0030] Examples and comparative examples relating to the optical transmission element of the present invention will be described below with reference to FIG.

[0031] As materials for forming the core material 3, polyoxypropylene triol and polyoxypropylene diol are used as polymer polyols, and hexamethylene diisocyanate is used as a hydroxyl group reactive polyfunctional compound. As materials for forming the clad material 2, ethylene-tetrafluoroethylene copolymers containing adhesive functional groups consisting of carboxylic anhydride residues are used. As fine particles, hexagonal plate-shaped zinc oxide with an average particle size of 1000 nm is used. The fine particles are mixed with the material for the clad material 2 so as to be 0.44 wt%, and then extrusion molding is performed to obtain a tube-shaped clad material 2 with a diameter of 3.0 mm. In a state where the clad material 2 is wound around a bobbin with a diameter of 300 mm, the material for forming the core material 3 is mixed and filled in the clad material 2, and the core material 3 is subjected to a non-fluidizing treatment by heating at 100°C or 110°C. In this way, the core material 3 and the clad material 2 are formed from the inside, and both ends are cut to obtain an optical transmission body 1 according to Example 1. Moreover, the above-mentioned fine particles were mixed into the core material 3, not into the cladding material 2, so as to be 0.13 wt %, to obtain the optical transmission body 1 according to Example 2. Moreover, a vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer was used as the material constituting the cladding material 2, and the other conditions were the same as those of the above-mentioned Example 1, to obtain the optical transmission body 1 according to Comparative Example 1. Moreover, a tetrafluoroethylene-hexafluoropropylene copolymer was used as the material constituting the cladding material 2, and the other conditions were the same as those of the above-mentioned Example 2, to obtain the optical transmission body 1 according to Comparative Example 2.

[0032] In order to evaluate the characteristics of the optical transmission bodies according to the above-mentioned Examples and Comparative Examples, the following tests were carried out.

[0033] (Lengthwise brightness measurement) Each sample was arranged in a straight line at 1000 mm and the brightness on the side was measured. The white LED as the light source was set as the origin, and the side brightness at a specified position from there was measured with an imaging color luminance meter for comparative verification. The results of the examples and comparative examples are shown in Figure 2. (Length direction color measurement) Each sample was arranged in a straight line at 1000 mm length and the chromaticity was measured on the side. The white LED as the light source was set as the origin, and the chromaticity of the side at a specified position from that was measured with an imaging color luminance meter for comparative verification. The results of the examples and comparative examples are shown in Figure 3. (Bending reaction force measurement) For each sample of 1000 mm, the positions 100 mm from the end and 700 mm from the end are fixed to the push-pull meter, and the position 400 mm from the end is fixed to the wall. The sample is arranged in a circular ring shape perpendicular to the wall, and the measurement start position is the position where the distance between the fixed part of the push-pull meter and the fixed part of the wall is 160 mm. From there, the push-pull meter is moved closer to the wall, and the maximum load when it is moved until the distance between the fixed part of the push-pull meter and the fixed part of the wall is 150 mm is taken as the measured value of the bending reaction force. The results of the examples and comparative examples are shown in Figure 4. (Comparison of adhesive strength between core material 3 and clad material 2 by thermal shock test) For each sample of 500 mm, the optical transmission body 1 was repeatedly subjected to a thermal history of 4 cycles of 100°C x 24Hr -40°C x 24Hr in a thermal shock tester, and the presence or absence of delamination between the core material 3 and the clad material 2 after the test was confirmed. As a result, in Example 1 and Example 2, no delamination was observed after the test, while in Comparative Example 2, in addition to the delamination that was confirmed before the test, an increase in the number of delaminations was confirmed after the test. From this result, it was found that in the case of Example 1 and Example 2, the durability against thermal shock was improved due to the strong adhesion between the core material 3 and the clad material 2. In other words, it was strongly suggested that in an ethylene-tetrafluoroethylene copolymer, which is usually poor in adhesion to multiple resins, by containing a carboxylic anhydride residue as an adhesive functional group, it reacts with the hydroxyl group contained in the core material 3 to form a strong chemical bond. (Confirmation of chemical adhesion between core material 3 and clad material 2 by infrared spectroscopy) In the optical transmission body 1, the inner surface of the tube-shaped cladding material 2 was measured by the total reflection measurement method of a Fourier transform infrared spectrophotometer to confirm whether the hydroxyl group contained in the core material 3 and the carboxylic anhydride residue contained in the cladding material 2 reacted to form a chemical bond. The sample of the above-mentioned Example 1 was used as the measurement sample, and the inner surface (A) of the cladding material 2 before being filled with the material constituting the core material 3, and the inner surface (B) of the cladding material 2 of the optical transmission body 1 filled with the core material 3 and subjected to a non-fluidizing treatment were measured. The inner surface (B) of the cladding material 2 of the optical transmission body 1 cannot be measured as it is, but the inner surface of the cladding material 2 can be measured by making a cut in the surface of the optical transmission body 1 and peeling off the core material 3 and the cladding material 2. As a result of the measurement, in (A), a 1794 cm -1 , 1870cm -1 Two absorption bands were confirmed, but in (B) the 1870 cm -1 The absorption band at 1697 cm disappears, and -1 It was confirmed that a new absorption band appeared at the 1000 nm region. This indicates that the hydroxyl groups of the core material 3 reacted with the carboxylic anhydride residues of the cladding material 2 during the non-fluidization treatment, changing the carboxylic anhydride residues to ester groups and carboxy groups, forming a chemical bond. The results of Example 1 are shown in Figure 5.

[0034] From these test results, the following was found. First, it was confirmed that the optical transmission body according to this embodiment can obtain sufficient brightness not only near the light source but also at a position far from the light source. In addition, it was confirmed that the chromaticity of both Example 1 and Example 2 was sufficiently distinguishable as white to the naked eye. However, it was confirmed that Example 2 in which the fine particles were dispersed in the core material 3 was yellower in the measured value than Example 1 in which the fine particles were dispersed in the clad material 2. In addition, in the measurement of the bending reaction force, it was confirmed that both Example 1 and Example 2 had flexibility that was not problematic in terms of practical specifications. In addition, both Example 1 and Example 2 had improved durability against delamination between the core material 3 and the clad material 2 against thermal shock compared to Comparative Example 2, and it was suggested that this improvement in durability was due to the strong adhesion between the core material 3 and the clad material 2. Furthermore, it was revealed by infrared spectroscopy that the core material 3 and the clad material 2 were chemically bonded to each other, and it was concluded that the improvement in durability against the above-mentioned thermal shock was due to the strong adhesion between the core material 3 and the clad material 2 by this chemical adhesion. [Industrial Applicability]

[0035] As described above in detail, the optical transmission body of the present invention can provide an optical transmission body having excellent durability. Therefore, this optical transmission body can be suitably used as illumination or lighting for mobile phones, digital cameras, personal computers, computer peripherals, wristwatches, car audio, car navigation systems, pachinko machines, slot machines, vending machines, automobile interiors, vehicle interior and exterior lighting, dog collars, ornaments, kitchens, traffic signs, washbasins, showers, bathtub temperature indicators, office equipment, household electrical appliances, optical equipment, various building materials, stairs, handrails, train platforms, outdoor signs, and the like, as well as backlights for liquid crystal displays. In addition, this optical transmission body can be combined with a light source and used as a lighting device for various illuminations and lighting facilities. [Explanation of symbols]

[0036] 1. Optical transmission body 2. Clad Materials 3 Core material

Claims

1. An optical transmission body comprising a tubular clad material and a core material housed in the clad material and having a refractive index higher than that of the clad material, The optical transmission body is characterized in that the cladding material is made of a fluororesin containing an adhesive functional group.

2. 2. The optical transmission member according to claim 1, wherein the fluororesin having the adhesive functional group introduced therein is an ethylene-tetrafluoroethylene copolymer containing a carboxylic anhydride residue.

3. 2. The optical transmission element according to claim 1, wherein the melting point of said cladding material is 190°C to 240°C.

4. 4. The optical transmission member according to claim 1, wherein fine particles are dispersed in the cladding material.

5. 5. An illumination device comprising a light source and the light transmitting member according to claim 4.

Citation Information

Patent Citations

  • JP1974028760A

  • Unsaturated polyester resin composition

    JP1978041391A

  • Power transmission device for vehicle

    JP1988076948A

  • Optical transmission member and illumination device using the same

    JP2004333539A

  • Side emission optical fiber and light emitting apparatus

    JP2006317844A